Ecology of Man at the Turn of Centuries - Wolański, Napoleon (Anthropological Review, 1987)
Human ecology is recognized as a research subject connected with biological and social effects of man’s impact on nature, and adaptation of man to changing environment; as point of view in creation of ecological harmony in contemporary world; but also as level of mind (attitude) in understanding of man-environment interrelation. As sciences human ecology is an interdisciplinary branch which is integrating biological and social studies on dynamic interrelation between people (as human beings, as populations-, and as any kind of society), but also as interrelation between man and his total (natural, social and man-made) environment. Main problems of contemporary human ecology are: 1) philosophy of human environment, and related theoretical problems, 2) biological and social problems of environment of origin and development of Man, 3) ecological problems of human biology (environmental physiology, population genetics, biodemography – environmental aspects), 4) problems of education for environment, and ecological strategy of survival of human species and development of society.